Data driven urbanism: challenges in implementing open data policy and digital transparency in the City of Cape Town - Dlamini, Majaha (Department of Environmental and Geographical Science, 2020)
As part of its quest to become the first digital African city, in 2014 the City of Cape Town adopted an open data policy, which was later coupled with an open data portal to make government data available for public access. This was touted as a novelty initiative as the City of Cape Town was the first African city to implement a policy of this nature. This open data initiative aimed at enhancing transparency and accountability as well as promoting inclusive economic participation for its citizens. Open data project managers from the city and external industry experts working on open data initiatives were interviewed to understand the current the state of open data within the city and how it worked with other stakeholders. The study draws on these interviews to present the current challenges experienced by the city from the city’s official point of view as well as from open data experts working closely with the city. To understand the practical experiences of how the city publishes data in its platforms, the study also extensively explored the city’s open data portal, as well as examining and commenting on the documented open data policy guidelines contrasted and compared to current practical experiences. To guide the objectives and analysis of the study, four key themes were adopted from literature; context, use, data and impact. Context focused on the overall context or environment at which open data in the city is provided as a public service, while use focused challenges on the uses of open data as well as it is users, data focused on the types of datasets published on the portal as well as the technical challenges in publishing them. Lastly impact looked at the expected benefits and goals of the city’s open data policy. The study through the themes highlighted the ongoing challenges at various levels that the city experience as they implement and develop the open data policy. Overall it was noted that open data was not a goal but continuous challenges were arising daily while implementing and developing the policy- while it was noted that various stakeholders within and outside government had to collaborate to effectively meet the required open data standards.